EVALUATION OF THE LEACHATE MANAGEMENT SYSTEM AT THE TAMANGAPA LANDFILL, MAKASSAR - Irham, Andi Muhammad; Soedjono, Eddy Setiadi (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2026)
The Tamangapa Landfill in Makassar receives more than 800 tons of solid waste per day under an open dumping system. This condition leads to leachate accumulation exceeding the available infrastructure capacity. Functional failures of the Leachate Treatment Plant (LTP) result in suboptimal treatment, causing leachate to be discharged directly into the environment. Therefore, immediate technical intervention is required. This study applies the Thornthwaite–Mather water balance method to estimate leachate discharge. In addition, laboratory analyses are conducted to evaluate influent and effluent quality based on regulatory standards. The results indicate that the LTP performance is highly ineffective, with an organic load removal efficiency of only 42%. Effluent concentrations of BOD (264.16 mg/L), COD (660.21 mg/L), and Total Nitrogen (161.65 mg/L) exceed the standards specified in PermenLHK No. 59/2016. The system failure is primarily attributed to structural and operational constraints, particularly excessive sludge accumulation and short-circuiting within the treatment ponds. Therefore, technical rehabilitation is required, including sludge dredging, installation of hydraulic baffles, and integration of advanced chemical treatment using the Fenton method to ensure compliance with effluent quality standards prior to environmental discharge.